Planet of the lawn gnomes - Stine, R. L. (New York : Scholastic, 2012)
Jay Gardener is trying to stay out of trouble in his new neighborhood, but when strange things keep happening to him, he wonders if it is the lawn gnomes causing all the trouble.
4.1
3-6.
3-6
Keywords: Garden ornaments and furniture -- Juvenile fiction; Gnomes -- Juvenile fiction; Garden ornaments and furniture -- Fiction; Gnomes -- Fiction; Horror stories; Garden ornaments and furniture -- Fiction; Gnomes -- Fiction; Horror fiction; Horror fiction